Trust in Government and COVID-19 Response Policy: A Comparative Approach. Issue 2 (4th March 2023) - Stanica, Cristina; Crosby, Andrew; Larson, Sarah
Abstract: As nations work to respond to COVID-19, trust in government is critical to achieving health outcomes. Studies argue that greater trust in government is associated with increased compliance with COVID-19 public health policies. This analysis investigated predictors of public trust during COVID-19 in 16 countries grouped in four regions. The data used (n = 47, 000) are taken from the Worldwide COVID-19 Attitudes and Beliefs dataset. Five hypotheses test the effects of stringency, geographic location, age, gender, income, and education levels on public trust. Findings reveal that increased stringency measures and education levels are positively associated with trust.